Network Pharmacology-based Analysis on the Molecular Biological Mechanisms of Xin Hui Tong Formula in Coronary Heart Disease Treatment - Wu Hua-Ying; Zhang Chen; Wang Zhao-Hua; Zhang Shi-Ying; Li Jing; Li Feng; Huang Hui-Yong; Li Liang (KeAi Communications Co., Ltd., 2019)
Objective: To investigate the potential molecular mechanism of Xin Hui Tong Formula (XHTF) in the treatment of coronary heart disease (CHD) by using network pharmacology and bioinformatics. Methods: The targets network of CHD was constructed through Therapeutic Targets Database (TTD) and Drugbank database; The XHTF pharmacodynamic molecule-targets network and the XHTF pharmacodynamic molecule-CHD targets network were explored by the traditional Chinese medicine systems pharmacology database and analysis platform (TCMSP). And the multi-targets mechanism and molecular regulation network of XHTF in the treatment of CHD were explored from multiple perspectives by Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) database pathway enrichment analysis. Results: A total of 88 CHD targets were screened out through the Therapeutic Targets and the Drugbank database. 393 compounds and corresponding 205 drug targets of XHTF were retrieved from TCMSP. A total of 13 known targets directly related to the development of CHD were retrieved from the disease-related databases: TP53, MAPK14, NFKB1, HSPA5, PLG, PTGS2, ADRB1, NOS2, CYP3A4, GRIA2, CYP2A6, GRIA1, PTGS1. XHTF also contained 118 drug targets that directly interact with CHD targets. GO enrichment analysis showed that the biological processes of 13 direct targets proteins were found to be mainly enriched in response to drug, cellular response to biotic stimulus, long-chain fatty acid metabolic process, fatty acid metabolic process and regulation of blood pressure. KEGG pathway enrichment analysis found that XHTF participated in the CHD pathological process mainly through retrograde endocannabinoid signaling, regulation of lipolysis in adipocytes, cAMP signaling pathway, chemical carcinogenesis and other pathways. Conclusions: XHTF plays a role in the treatment of CHD through multiple targets and multiple pathways, and provides a scientific basis for the theory of "virtual standard" in the treatment of CHD. Keywords: Xin Hui Tong Formula (XHTF), Coronary heart disease, Network pharmacology, Network analysis, Bioinformatics